A New Spanish Generation in Germany. Analysis of the Motivations to Leave under the Veil of the Crisis - Pérez-Caramés, Antía (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2017)
This article deals with the study of the new South-North European migration process within a context characterized by the economic crisis and an unprecedented rise in unemployment. More specifically, it addresses the phenomenon of Spaniards emigrating to Hamburg, Germany, since 2008. The main objective is to analyse the motivations to leave, contextualizing them within larger socio-structural processes, altogether with a study of the perceptions this community has on the profile and characteristics of this migratory wave. The methodological approach for this research is of a qualitative nature, based on semi-structured interviews to recent Spanish emigrants in Hamburg (Germany), follow-up of virtual communities and participant observation.